Constraining Microfractures in Foliated Alpine Fault Rocks With Laser Ultrasonics. Issue 8 (21st April 2020) - Simpson, Jonathan; Adam, Ludmila; van Wijk, Kasper; Charoensawan, Jirapat
Abstract: Quantifying the amount and alignment of microfractures is important to understand the geomechanics, fluid flow, and seismic imaging of fault zones. At the Alpine Fault, New Zealand, the preferred alignment of minerals, foliation, and fractures results in elastic wave anisotropy. We have designed a unique laser‐ultrasonic laboratory setup to study Alpine Fault rock samples at upper crustal conditions. Combined with differential effective medium modeling, we distinguish microfracture porosity and orientation from mineral alignment, as a function of distance to the principal slip zone (PSZ). Nearest to the PSZ, the cataclasite has the lowest P wave anisotropy with the most (randomly oriented) fractures. Next, the ultramylonite exhibits the greatest P wave anisotropy (∼45%) with 40% of its fractures aligned with foliation. Further from the PSZ, P wave anisotropy is 14–19% on average, due to 20–30% of the fractures being oriented in the same direction as mineral alignment. Plain Language Summary: The movement on faults causes fractures and alignment of minerals in the adjacent rocks. This causes seismic waves to travel fastest parallel to these features, a phenomenon known as anisotropy. Quantifying the amount and orientation of the fractures that contribute to this anisotropy is important for understanding fault zones and the processes which could influence the nature of earthquakes. However, this requires a method that can separate the effects of the fractures from those of the minerals. We have designed a system that uses laser ultrasonics to measure the speed of waves through rocks under pressure at spatially dense locations. We combine these measurements with numerical modeling, allowing us to accurately quantify the amount and orientation of fractures in rocks from the Alpine Fault, New Zealand. We find that the total amount of fractures increases toward the fault. Additionally, the amount of fractures aligned with the fault plane (up to 40%) increases toward the fault until the fractures become almost completely randomly oriented for the cataclasite in the core of the fault. Key Points: We present a new method combining laser ultrasonics with DEM modeling to separate effects of microfractures from mineral foliation Microfracture porosity is generally small at the Alpine Fault but increases toward the principal slip zone Up to 40% of fractures are aligned with the foliation in the schist and mylonites while fractures are randomly oriented in the cataclasite